Quality of Life During Neoadjuvant Treatment and After Surgery for Resectable Esophageal Carcinoma - van Meerten, Esther; van der Gaast, Ate; Looman, Caspar W.N.; Tilanus, Hugo W.G.; Muller, Karin; Essink-Bot, Marie-Louise (International journal of radiation oncology, biology, physics, 2008)
Because of the trade-off between the potentially negative quality-of-life (QoL) effects and uncertain favorable survival effect of neoadjuvant chemoradiotherapy (CRT) in patients with resectable esophageal cancer, we assessed heath-related QoL (HRQoL) for up to 1 year postoperatively in these patients treated with preoperative CRT with a non–platinum-based outpatient regimen followed by esophagectomy. Patients undergoing neoadjuvant paclitaxel and carboplatin therapy concurrent with radiotherapy followed by surgery completed standardized HRQoL questionnaires before and after CRT and at regular times up to 1 year postoperatively. We analyzed differences in generic Qol core questionnaire [QLQ-C30] and condition-specific (esophageal site-specific [OES-18]) HRQoL scores over time by using a linear mixed-effects model. Mean scores of most HRQoL scales deteriorated significantly during neoadjuvant CRT. The largest deterioration was observed for physical and role-functioning scales. All except two symptom scores worsened significantly. Postoperatively, most mean HRQoL scores improved until recovery to baseline level. Speed of improvement varied. Average taste score returned to baseline 3 months postoperatively, whereas it took 1 year for the average role-functioning score to restore. The emotional-functioning score showed a different pattern; it was worst at baseline and increased over time during CRT and postoperatively. Dysphagia and pain scores worsened considerably during CRT, restored to baseline 3 months postoperatively, and were even significantly better 1 year postoperatively. Preoperative CRT with paclitaxel and carboplatin for patients with resectable esophageal cancer had a considerable temporary negative effect on most aspects of HRQoL. Nonetheless, all HRQoL scores were restored or even improved 1 year postoperatively.